Naproxen-induced pseudolymphoma syndrome: a case report - Shang-Hong Lin; Cheng-Yu Wang; Ji-Chen Ho; Wei-Ming Wu (Wolters Kluwer Medknow Publications, 2010)
Drug-induced pseudolymphoma syndrome is a rare form of adverse cutaneous drug reaction. Its clinical and histological presentation may mimic mycosis fungoides, which sometimes leads to misdiagnosis and unnecessary treatments. We describe the case of a 65-year-old man with a generalized pruritic and confluent maculopapular eruption. His history of skin lesions was concordant with medication and resolved after discontinuation. However, microscopic examination showed characteristic features of mycosis fungoides, including Pautrier-like microabscesses and cerebriform nuclei of atypical lymphocytes. The immunohistochemical study showed CD4/CD8 infiltrate ratio to be 1 in the epidermis. The histopathological result of a second skin biopsy was compatible with drug eruption. This experience demonstrates that combining clinical history, histological and immunohistochemical findings is crucial for a definite diagnosis of PLS.